PSYCHOLOGICAL PROBLEMS OF SEX EDUCATION FOR ADOLESCENTS - Bakhramova Abira Abdullaevna (Journal of Artificial Intelligence and Digital Economy, 2024)
The article discusses the problem of sex education for adolescents as one of the most pressing problems in Uzbek education. The author concludes that sex education policies and programs should be developed on the basis of evidence-based theories related to modern theories of youth development. In addition, there is an urgent need to equip teachers, social workers, doctors, and parents with the skills needed to improve the effectiveness of sex education programmes. The author believes that to gain a more informed understanding of what factors contribute to program effectiveness, methodologically rigorous evaluation studies using both quantitative and qualitative methods should be used